THE IMPLEMENTATION OF ACTIVE LEARNING MODELS TO INCREASE PRE-SERVICE TEACHERS’ HIGH ORDER THINKING SKILLS - Sulastri, Yayu Laila; Wahidin, Didin; Muchtar, Hendi Suhendraya; Lestari, Zubaedah Wiji (PEOPLE: International Journal of Social Sciences, 2016)
Teaching Practice is a compulsory subject that must be followed by the 6th semester students of Faculty of Teachers’ Training and Educational Sciences in Universitas Islam Nusantara, Bandung, Indonesia. The subject has 4 credits that consist of series activities in form of theory and teaching simulation. The objective of the subject is to establish pre-service teacher knowledge and skills by brushing up pre-service teacher knowledge and apply the theory into real class situation. However, based on observations and informal interviews, many students are not yet ready to do teaching practice and their High Order Thinking Skills (HOTS) are still low. The purpose of this study is to implement active learning models in preparing pre service’s teacher and increasing their HOTS. Moreover, the study also investigates the effectiveness of some active learning models. This study implemented Research and Development design. The first phase design is a preliminary study carried out by applying qualitative descriptive approach. The second phase is the development of model design and teaching materials, followed by limited scope trial by applying experimental method (Single One Shot Case Study). The limited trial shows that pre-service teacher’s HOTS mostly increase in “analysis” indicator. The limited trial also show that the average score of guided discovery learning model using role playing and making a direction are higher than four other learning models. Based on the finding it could be concluded that four guided discovery learning models implemented in this study improved pre-service teachers’ HOTS. However, the content of material and the design of learning activities still make the students confuse, as it needs some improvement.